Using concept maps to evaluate preservice biology teachers’ conceptualization of COVID-19 as a complex phenomenon - Bielik, Tom; Jagemann, Johannes; Krell, Moritz; Krüger, Dirk; Ben Zvi Assaraf, Orit (Frontiers in Education, 2023)
Introduction The COVID-19 pandemic showed the critical importance of supporting teachers’ and students’ systems thinking when making sense of complex phenomena. This study sets to explore preservice biology teachers’ (PBTs) mental models of COVID-19 as complex phenomenon using concept maps. Methods 27 PBTs concept maps of COVID-19 outbreak were collected and taken for analysis. Structural and complexity attributes were identified in participants’ concept maps and the relationships between them were tested, providing statistical analyses using exemplary concept maps. Results The results suggest that the appearance of many concepts in a map (structural attribute) does not necessarily indicate high level of complexity, but rather the amount of simple structural relationships (complexity attribute). On the other hand, the results indicate that higher structural sophistication (e.g., high number of connections and junctions) could be associated with the complexity level of the map. Discussion This study provides a practical method for evaluating the complexity level of PBTs’ systems thinking, suggests a possible link between structural and complexity attributes in their concept maps, and demonstrates the need to further support PBTs in developing their systems thinking skills in the context of complex biological phenomena.